Evaluating browsing damage to selected taxa in a trial plantation within the Lungmanis Forest Reserve, Sabah, Malaysia - RICHARD J. MAJAPUN; VIVIANNYE PAUL; MOHD. AMINUR FAIZ SUIS; EYEN KHOO; VERONICA S. GUANIH; PANG KAT NYEN KELVIN; CHEN THAU EN; MARIA AJIK (Society for Indonesian Biodiversity, 2024)
Abstract. Majapun RJ, Paul V, Suis MAF, Khoo E, Guanih VS, Kelvin PKN, En CT, Ajik M. 2024. Evaluating browsing damage to selected taxa in a trial plantation within the Lungmanis Forest Reserve, Sabah, Malaysia. Biodiversitas 25: 3540-3554. The study assessed the impact of wildlife pests on seven tree taxa, including Acacia crassicarpa, Eucalyptus pellita, Falcataria moluccana, Khaya ivorensis, Neolamarckia cadamba, Terminalia copelandii, and Swietenia macrophylla, in trial plantations within Sabah's Lungmanis Forest Reserve, Sabah, Malaysia. Browsing damage was measured for all taxa at two time points (t1 and t2) using three indices (H-Index, S-Index, and PS-Index). The study revealed that E. pellita, A. crassicarpa, and K. ivorensis resisted browsing damage. At the same time, other species, such as N. cadamba and F. moluccana, suffered significant damage, with tree height losses between 50% and 70% due to wildlife pest activity. The study recorded high damage intensity for the PS-Index in the